2016
DOI: 10.3389/fpls.2016.01837
|View full text |Cite
|
Sign up to set email alerts
|

MtNF-YA1, A Central Transcriptional Regulator of Symbiotic Nodule Development, Is Also a Determinant of Medicago truncatula Susceptibility toward a Root Pathogen

Abstract: Plant NF-Y transcription factors control a wide array of biological functions enabling appropriate reproductive and developmental processes as well as adaptation to various abiotic and biotic environments. In Medicago truncatula, MtNF-YA1 was previously identified as a key determinant for nodule development and establishment of rhizobial symbiosis. Here, we highlight a new role for this protein in compatibility to Aphanomyces euteiches, a root pathogenic oomycete. The Mtnf-ya1-1 mutant plants showed better sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 76 publications
1
12
0
Order By: Relevance
“…In both root types, about two-thirds of the DEGs were upregulated and one-third was downregulated. These numbers are similar to those obtained after infection for 24 h (Badis et al, 2015;Rey et al, 2016). The overlay between DEGs obtained in our approach and those obtained after infection for 24 h, however, is rather small, pointing to the fact that roots responded differently to the infection with A. euteiches at these two time points (Supplemental Fig.…”
Section: Inoculation With a Euteiches For 2 H Alters The Transcriptosupporting
confidence: 84%
“…In both root types, about two-thirds of the DEGs were upregulated and one-third was downregulated. These numbers are similar to those obtained after infection for 24 h (Badis et al, 2015;Rey et al, 2016). The overlay between DEGs obtained in our approach and those obtained after infection for 24 h, however, is rather small, pointing to the fact that roots responded differently to the infection with A. euteiches at these two time points (Supplemental Fig.…”
Section: Inoculation With a Euteiches For 2 H Alters The Transcriptosupporting
confidence: 84%
“…Forward genetics of M. truncatula identified the dual contribution of a glycerol phosphate acyl transferase gene termed RAM2 ( Reduced Arbuscular Mycorrhization 2 ) in the colonization by AM fungi and the oomycete pathogens P. palmivora ( Wang et al , 2012 ) and Aphanomyces euteiches ( Gobbato et al , 2013 ). Complementarily, reverse genetics approaches based on surveying mutants defective in symbiosis for their interaction with pathogens revealed that symbiosis-related LysM-RLK receptors, transcription factors, and hormone signalling genes may have broader functions in the associations with microbes ( Laffont et al , 2015 ; Moreau et al , 2013; Rey et al , 2013 , 2015 , 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The overexpression of OsHAP2E for a CCAAT-binding factor confers resistance to Cucumber mosaic virus and Rice necrosis mosaic virus [41]. MtNF-YA1 , previously identified as a key regulator of rhizobial symbiosis establishment, is also a determinant of Medicago truncatula susceptibility toward a root pathogen [42]. In summary, our results showed that some members in the miR169 family might regulate NF-Y transcription factors to activate the ISR process.…”
Section: Discussionmentioning
confidence: 71%